2010
DOI: 10.1002/tox.20648
|View full text |Cite
|
Sign up to set email alerts
|

Antiapoptotic efficacy of folic acid and vitamin B12 against arsenic‐induced toxicity

Abstract: Earlier, we proposed that the ability of folic acid and vitamin B₁₂ to preserve systemic and mitochondrial function after short-term exposure to arsenic may prevent further progression to more permanent injury and pathological changes leading to cell death. To elucidate its mechanism, the present study examined the antiapoptotic efficacy of folic acid and vitamin B₁₂ against short-term arsenic exposure-induced hepatic mitochondria oxidative stress and dysfunction. Sixteen to eighteen weeks old male albino rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 62 publications
2
26
0
Order By: Relevance
“…Cobalamin is a cobalt-coordinated tetra pyrrole and is used as an enzyme cofactor in prokaryotes. However, it has also been reported to restore the activity of other ROS scavenging proteins (Majumdar et al 2012; Chattopadhyay et al 2012) that were found in the genome, namely catalase (Acife_2431) and superoxide dismutase (Acife_1434). Its genomic production potentially includes three cobalt transporters (Acife_0490, Acife_1063, and Acife_2190), as well as the cobalamin biosynthesis proteins CobS (Acife_2993), CbiX (Acife_2081), and two copies of CbiA (Acife_1891 and Acife_3125).…”
Section: Resultsmentioning
confidence: 99%
“…Cobalamin is a cobalt-coordinated tetra pyrrole and is used as an enzyme cofactor in prokaryotes. However, it has also been reported to restore the activity of other ROS scavenging proteins (Majumdar et al 2012; Chattopadhyay et al 2012) that were found in the genome, namely catalase (Acife_2431) and superoxide dismutase (Acife_1434). Its genomic production potentially includes three cobalt transporters (Acife_0490, Acife_1063, and Acife_2190), as well as the cobalamin biosynthesis proteins CobS (Acife_2993), CbiX (Acife_2081), and two copies of CbiA (Acife_1891 and Acife_3125).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, 74% increase in the sperm count in the men reported after administration of the FA. Also, FA (3 mg/day for 3 months) improved spermatozoa number and motility in infertile men 29 . FA could protect cells against damage caused by lead 32 .…”
mentioning
confidence: 89%
“…However, Raigani reported FA supplementation did not ameliorate sperm quality in infertile men 28 . The FA successfully alleviated the SOD, GPx depletion and MDA elevation 29 . In this study, dose dependent increase observed on spermatozoa mobility, mortality (%) using different levels of the FA (2, 5 and 10 mg/kg) treated rat (Figures 2-3).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Preliminary evidence indicates that folic acid and vitamin B12 have anti-apoptotic efficacy and the ability to preserve mitochondrial function (25). Furthermore, vitamin B11 deficiency has been associated with elevated concentrations of homocysteine in the plasma of elderly non-demented patients (26,27).…”
Section: Introductionmentioning
confidence: 99%